A comparison of methods for approximating periodic limit cycles in nonlinear systems with joint friction. Issue 1 (17th December 2018) - Kappauf, Jonas; Hetzler, Hartmut
Abstract: In this contribution, approximation methods for calculating periodic limit cycles of self‐excited dynamical systems with frictional damping are studied. In industrial application, e.g. the analysis of brake squeal, the so‐called Energy‐Balance has attracted a lot of interest [3], while rather classical Harmonic Balance methods are commonly used in non‐linear analysis. Focussing on the effect of both smooth and non‐smooth non‐linearities, limit cycles were calculated for two minimal models, which are commonly used when dealing with NVH or brake squeal analysis. Moreover these two methods are compared in terms of accuracy and numerical effort.